IMPLEMENTATION OF GENDER POLICY IN SOCIETY TRANSFORMATION (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This thesis analyzes the theoretical and practical aspects of the formation and effective implementation of gender policy in the process of social transformation. It is emphasized that the issue of ensuring gender equality is of great importance for the democratic and social development of Uzbekistan, especially the role of the gender approach in the reforms carried out within the framework of the "New Uzbekistan" concept is expanding. The activity of women in socio-political life, their role in education and employment, use of digital opportunities, as well as the position of men on gender issues in a transforming society are discussed.